2017
DOI: 10.18632/oncotarget.16282
|View full text |Cite
|
Sign up to set email alerts
|

The pancreas responds to remote damage and systemic stress by secretion of the pancreatic secretory proteins PSP/regI and PAP/regIII

Abstract: IntroductionIn patients with infection and sepsis serum levels of Pancreatic Stone protein/regenerating protein I (PSP) are highly elevated. The origin of PSP during these conditions is presumably the pancreas, however, an intestinal origin cannot be excluded. Similarly, pancreatitis-associated protein (PAP) was identified in the pancreas. These proteins were also localized in intestinal organs. Here we aim to elucidate the bio-distribution of PSP and PAP in animal models of sepsis and in healthy humans.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
(37 reference statements)
0
26
0
Order By: Relevance
“…Analysis of RNA-Seq data derived from Barkbase ( 32 ) revealed marked differences in expression of REG3E RNA between tissues, with the highest number of reads found in the pancreas, followed by the cardiac atrium and the small intestine. In humans and rodents, REG1A protein is predominantly produced in the pancreas, whereas REG3A is primarily found in the small intestine ( 35 ). This is paralleled by findings in lambs, where a “PAP-like protein” mRNA was expressed 300-fold higher in ileal and jejunal Peyer's patches compared to the pancreas ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of RNA-Seq data derived from Barkbase ( 32 ) revealed marked differences in expression of REG3E RNA between tissues, with the highest number of reads found in the pancreas, followed by the cardiac atrium and the small intestine. In humans and rodents, REG1A protein is predominantly produced in the pancreas, whereas REG3A is primarily found in the small intestine ( 35 ). This is paralleled by findings in lambs, where a “PAP-like protein” mRNA was expressed 300-fold higher in ileal and jejunal Peyer's patches compared to the pancreas ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant human REG1A and REG3A proteins, produced in Pichia pastoris culture, and antibodies raised in rabbits and guinea pigs against human recombinant REG1A and REG3A as previously described ( 6 , 34 , 35 ) were obtained from the Pancreas Research Laboratory, University of Zürich, Switzerland.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation was then clinically confirmed in a cohort of trauma patients, in which serum PSP rises early after trauma for those patients that later develop infection and sepsis [29]. Reding et al further showed that the pancreas senses remote organ damage and systemic stress and responds by secreting PSP, particularly when associated with septic complications [30].…”
Section: The Pancreatic Stone Protein: Structure Function and Its Role In Sepsismentioning
confidence: 90%
“…This observation was then clinically confirmed by the demonstration in humans that the pancreas senses remote organ damage and systemic stress and responds by secreting PSP in the absence of pancreatic tissue damage [34]. As an acute-phase protein, PSP might be involved in promoting cell proliferation during regenerative processes [35], through regulation by IL-6 and other cytokines that are released after tissue injury [36,37], rendering to the pancreas what Reding et al [38] call "the role of an acute phase organ".…”
Section: Pancreatic Stone Protein (Psp): Structure Function and Kineticsmentioning
confidence: 95%